Asuhan Keperawatan Psikososial Pada Wanita Dewasa Dalam Merawat Pasien Covid Dengan Terapi Dzikir : Asuhan Keperawatan Psikososial Pada Wanita Dewasa Dalam Merawat Pasien Covid Dengan Terapi Dzikir - Larasuci Arini (Akper Kesdam I/Bukit Barisan Padang, 2021)
Covid -19 an infectious disease caused by a new type of coronavirus with common symptoms of fever, weakness, stones, seizures, and diarrhea. The purpose of providing nursing care is to overcome anxiety in adult women who treat covid patients through dhikr therapy. This nursing care was carried out for three days from 25-27 October 2020. The research method used in nursing care is a case study which is carried out based on the stages of nursing care including assessment, diagnosis, intervention, implementation and evaluation of nursing. The results of this nursing care obtained two diagnoses, namely anxiety associated with changes in status and disturbances in sleep patterns associated with external factors of anxiety / fear. The intervention given to patients with priority problems, namely anxiety, is the dhikr therapy. This aims to reduce the anxiety experienced by clients while treating Covid patients, and can be seen after being given dzikir therapy for three days. It is hoped that after providing this care, all room nurses who are Muslim can apply non-pharmacological dzikir therapy to reduce anxiety while caring for Covid patients.